Midwives’ knowledge and perspectives on neonatal resuscitation and survival before and after Helping Babies Breathe training: a qualitative study in Uganda - Anna Bergstrom; Josaphat Byamugisha; Susanna Myrnerts Höök; Marielle Abrahamsson; Sarah Namusoko (BMJ Open)
Objectives Birth asphyxia is a significant factor contributing to neonatal mortality, particularly in low- and middle-income countries where most neonatal deaths occur. Encouraging women to deliver in hospitals has become a pivotal strategy. Numerous training programmes, such as Helping Babies Breathe (HBB), have been designed to impart neonatal resuscitation and infant care skills to support breathing at birth. Limited attention has been given to exploring the perspectives and experiences of midwives and their hospital managers in translating the acquired knowledge from these programmes into practice. This study aims to explores the understanding, perspectives, and first-hand experiences related to the factors impacting neonatal resuscitation practices and survival, both pre-HBB and post-HBB training.Design Qualitative individual interviews and focus group discussions study. A data-driven inductive content analysis approach was used for the analysis.Setting The high-risk labour ward and theatre at a National Referral Hospital, Uganda.Participants 45 clinically active midwives were enrolled; all had recently completed the HBB training programme.Intervention Semistructured individual interviews (n=2) and focus group discussions (n=43, distributed across seven groups) were held from 26 April to 4 May 2018. Discussions were audio-recorded and transcribed verbatim.Results Three emerging themes illustrated midwives’ knowledge, opinion on and experience of neonatal resuscitation and survival. Excessive workload, limited access to clean equipment, and ethical dilemmas hampered performance and neonatal survival. Midwives, facing inadequate support, strived to ensure patient safety. While HBB training addresses malpractices, additional training was needed.Conclusions Midwives had few opportunities to change their workload and improve their education. This highlights the need for a closer examination of the challenges faced by healthcare providers in ensuring effective neonatal resuscitation and survival in low-resource settings. To address this, we propose better routines for organising work, cleaning and maintaining equipment, and implementing better training routines.